Differences in Home Health Nursing Care for Patients with Parkinson’s Disease by Stage of Progress: Patients in Hoehn and Yahr Stages III, IV, and V - Yumi Iwasa; Izumi Saito; Miyoko Suzuki (Parkinson's Disease)
As societal aging progresses globally, the number of people with Parkinson’s disease (PD) is expected to increase worldwide. Accordingly, the need for home health nursing care for homebound patients with PD will continue to expand. We aimed to clarify the clinical care provided by nurses to homebound patients in each Hoehn and Yahr (HY) stage of the disease. We analyzed the visiting nursing records of patients and observed the clinical care provided by nurses in patients’ homes and nursing homes to compare the attributes of patients and differences in nursing care by HY stage. All 21 patients surveyed were at or above HY stage III. The nurses visited each patient nine times per month, on average. The number of visits was positively correlated with HY stage. All stage III patients were homebound, and medication dosage and dispensation assistance were quite common. Several stage IV patients were admitted into nursing homes. In stage V, assistance with hygiene, bedsore management, urine withdrawal/bladder catheters, and other excretory aids were among the most common forms of nursing care provided. As patients’ stages progressed, guidance/educational care meant to encourage self-care decreased and direct physical care increased. Clear differences in nursing care were observed between HY stages, suggesting that stage-based protocols regarding the nature and frequency of nursing visits may be useful for ensuring consistent, effective care of patients with PD.